Meeting notes: 11 February 1901 (Proceedings of the Society of Antiquaries of Scotland, 1901)
Meeting notes for 11 February 1901. Before the meeting began, the Vice-President presented an Address to King Edward VII following the death of his mother, Queen Victoria.